A feasibility analysis in incorporating low cost GNSS receivers for deformation monitoring in high rise buildings - Jayamanne, J.M.O. (2024)
High-rise buildings are prone to experiencing positional deformations due to environmental influences, such as thermal radiation and wind. The monitoring of such deformations is of utmost importance in guaranteeing the structural integrity of the structure and the safety of the buildings. The utilisation of Global Navigation Satellite Systems (GNSS) for deformation monitoring has become prevalent owing to their ability to furnish accurate and high-frequency data on varying coordinates. However, the frequent monitoring of high-rise structures is hindered by the excessive expenses linked with the utilisation of geodetic-grade GNSS receivers. Low-cost multi-frequency GNSS receivers have been identified as a prospective substitute for this challenge. In the beginning, receivers that were less expensive had certain limitations in terms of accuracy and signal quality when compared to geodetic-grade instruments. The aim of this research is to examine the viability of employing inexpensive GNSS receivers for the purpose of monitoring positional deformation in tall structures. The study aims to assess the accuracy and precision levels of low-cost GNSS receivers, conduct a comparative analysis of their performance against geodetic GNSS receivers in detecting minor positional deviations, and investigate the feasibility of integrating low-cost GNSS receivers for monitoring deformations in tall structures. The results indicate that dual frequency low-cost receivers coupled with a geodetic antenna can reach the accuracy level of a geodetic receiver with a geodetic antenna with rigorous observation and data processing techniques. The single frequency low-cost receivers combined with low-cost antenna provides a lower accuracy, hence is not recommended for high-rise building monitoring. However, the accuracy of single frequency receivers can be enhanced significantly when coupled with a geodetic antenna. The results further indicate that a short baseline should be maintained as much as possible for an enhanced accuracy.